Pendampingan Implementasi Kurikulum Operasional Madrasah Di Madrasah Ibtidaiyah Hidayatut Tholibin - Mohammad Afifi; Zahriyah, Sofiatus (LP3M IAIFA Kediri, 2024)
Madrasah Ibtidaiyah Hidayatut Tholibin faces challenges in the implementation of the Madrasah Operational Curriculum (KOM) due to limited resources and lack of training for educators. The surrounding community with a lower middle economic background and a low level of parental education, is very dependent on this madrasah to provide quality basic education. This service program aims to provide intensive assistance to educators through the Asset-Based Community Development (ABCD) method. This approach includes five stages: Discovery, Dream, Design, Define, and Destiny. The results of the activity showed an increase in teachers' understanding and skills in compiling and implementing the curriculum, supported by the strengthening of relevant infrastructure. Continuous evaluation and monitoring ensure that the curriculum is implemented effectively, in line with educational objectives and student characteristics. In conclusion, this program has succeeded in improving the the quality of education at Madrasah Ibtidaiyah Hidayatut Tholibin through the implementation of a more targeted curriculum and in accordance with local needs.